Project Management Maturity Analysis as A Framework to Move Forward to Best Practices The Case of Group Project Management at PT. XYZ - Wahyuni, Henny; Firman, Aries F (The Indonesian Journal of Business Administration, 2012)
In this globalization era, good capability in project management is necessary for every telecommunication service provider to win the competition. PT. XYZ is trying to improve it’s way in project management to be able to compete and be the number 1 Telecommunication service provider in Indonesia and to do that the Top Management is focusing in Asset Management. The questions in this research are : How do the improvement taken right now align with Group PPM’s Strategic Plan ? and What are the impact from current group PPM’s positions to its strategic plan? This research is based on Quantitative approach using OPM3 to calculate degree of maturity, and Qualitative approach to find the root cause in asset management. From calculation and data analysis, Group PM’s actions is align with its strategic plan but its strategic plan is partially achieved because the implementation is not running as expected and there are root cause that has not been answered yet. The impact is, its strategic plan not running as expected and there is a delay possibility. This research recommends: Recommendation / solution from Root Cause Analysis, First priority and second priority from the OPM3 framework, Recommendation to complete Best Practices, and Time Frame to accomplish all Best Practices. Keywords: Root Cause, Project Management, OPM3 (Organizational Project Management Maturity Model)